Nahdlatul Ulama's Preaching Management in Strengthening Religious Moderation in Society - Nur Permai Pertiwi; Soiman Soiman (Suluah Pasaman, 2026)
This study aims to determine Nahdlatul Ulama's da'wah management in strengthening religious moderation in the Tanjung Pura District, Langkat Regency. The method used is qualitative research with a descriptive approach through observation, interviews, and documentation.The informants numbered 6 people, consisting of 1 administrator of the NU MWC Tanjung Pura District, 2 administrators of NU branches, 1 religious figure, and 2 community members involved in da'wah activities.The research results show that NU's da'wah management in Tanjung Pura District encompasses planning, organizing, implementing, monitoring, and evaluating functions, all systematically implemented. The da'wah program includes regular religious studies, socio-religious activities, and community development based on the values ​​of Ahlussunnah wal Jamaah. These efforts contribute to instilling attitudes of tolerance, tawassuth (religious tolerance), tawazun (religious tolerance), and i'tidal (compassionate adherence) within the community. The findings of this study are expected to serve as a reference for religious organizations in developing da'wah management that supports the strengthening of religious moderation and the creation of a harmonious community life.